Mitochondrial COI Sequence Variations within and among Geographic Samples of the Hemp Pest Psylliodes attenuata from China - Guo, Litao (Insects, 2020)
The hemp flea beetle Psylliodes attenuata (Coleoptera: Chrysomelidae: Psylliodes) is a common pest of Cannabis sativa, including cultivars of both industrial hemp and medicinal marijuana. Both the larval and adult stages of this beetle can cause significant damages to C. sativa, resulting in substantial crop losses. At present, little is known about the populations of this pest, including its genetic diversity. In this study, we obtained 281 P. attenuata samples from nine field sites representing broad industrial hemp productions in China and analyzed their DNA sequences at the mitochondrial COI gene, the insect DNA barcode. Our analyses revealed a total of 48 haplotypes, with 28 being found only in one specimen each while the remaining 20 were shared by two or more specimens each. Of the 20 shared haplotypes, eight were shared among local populations often from far away locations, consistent with recent long-distance dispersals. However, the observed putative long-distance dispersals have not obscured the significant genetic differentiations among the regional populations from northeastern, eastern, central and southwestern China. Interestingly, haplotype network analyses suggest evidence for potential mitochondrial recombination in natural populations of this species. We briefly discuss the implications of our results on its evolution, center of diversity, route of spread, and pest management strategies in hemp fields.